AB0251 Early Onset of Benefit by Patient-Reported Outcomes (PROs) with Sarilumab Treatment in RA. (15th July 2016) - Strand, V.; Chen, C.; Mahajan, P.; Kosinski, M.; Mangan, E.K.; van Hoogstraten, H.; Graham, N.; Lin, Y.; Keystone, E.; Braun, J.
Abstract : Background: Efficacy, including improvements in patient-reported outcomes (PROs), was demonstrated in 2 phase 3 trials, MOBILITY 1 (NCT01061736 ) and TARGET 2 (NCT01709578 ), of sarilumab, an investigational human anti–interleukin 6 receptor monoclonal antibody. The most common treatment-emergent adverse events in both studies were infections, neutropenia, injection site reactions, and increased transaminases. Objectives: To evaluate the early onset of benefit of sarilumab treatment measured by PROs. Methods: In both studies, adults with moderate-to-severe, active rheumatoid arthritis (RA) were randomized to 1 of 3 groups receiving placebo, sarilumab 150 mg, or sarilumab 200 mg subcutaneously (SC) every 2 weeks (q2w) plus methotrexate (MTX; MOBILITY) or conventional synthetic disease-modifying antirheumatic drugs (csDMARDs; TARGET). PROs assessed as early as week 2 included patient global assessment of disease activity (PtGA), pain assessed by visual analog scale (VAS), Health Assessment Questionnaire–Disability Index (HAQ-DI), Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-F), sleep by VAS (MOBILITY), and AM stiffness by VAS (TARGET). Changes from baseline were analyzed using mixed-model repeated measures with region, number of prior tumor necrosis factor inhibitors (TNFis) (TARGET) or prior biologic use (MOBILITY), visit, treatment, treatment-by-visit interaction, and baseline PRO scores as covariates. Results: Greater improvements were reported by patients treated with sarilumab 150 and 200 mg SC q2w vs placebo as early as week 2 in PtGA, pain VAS, HAQ-DI, FACIT-F, sleep VAS, and AM stiffness VAS (nominal P <0.05) (Figure ) and sustained through week 24. Between-group differences were statistically significant for FACIT-F and sleep VAS at week 24 in MOBILITY and for HAQ-DI at week 12 (TARGET) and week 16 (MOBILITY). Conclusions: Sarilumab treatment rapidly improved a broad range of PROs in patients with RA with inadequate response to MTX (MOBILITY) or TNFis (TARGET); these improvements were observed as early week 2 and maintained through week 24. The results demonstrate the early benefit of sarilumab treatment based on patients' own assessments of their disease. References: Genovese et al. Arthritis Rheumatol. 2015;67:1424–1437. Fleischmann et al. Arthritis Rheumatol. 2015;67(suppl 10). Acknowledgement: This study was sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: V. Strand Consultant for: AbbVie, Amgen, AstraZeneca, Biogen, BMS, Celgene, Celltrion, Consortium of Rheumatology Researchers of North America (CORRONA), Crescendo/Myriad Genetics, EMD Serono, Genentech/Roche, GSK, Janssen, Eli Lilly, Novartis, Pfizer Inc, Regeneron Pharmaceuticals, Inc, Sandoz, Sanofi, and UCB, C. Chen Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, P. Mahajan Shareholder of: Sanofi, Employee of: Sanofi, M. Kosinski Consultant for: Sanofi and Regeneron, E. Mangan Shareholder of: in Pfizer Inc and Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, H. van Hoogstraten Shareholder of: Sanofi, Employee of: Sanofi, N. Graham Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, Y. Lin Shareholder of: Sanofi, Employee of: Sanofi, E. Keystone Consultant for: has consulting agreements/advisory board membership with Abbott, AstraZeneca, Biotest, BMS, F. Hoffman-La Roche, Genentech, Janssen, Eli Lilly, Merck, Pfizer Inc, and UCB; and has speaker honoraria agreements with Abbott, Amgen, AstraZeneca, BMS Canada, F. Hoffman-La Roche, Janssen, Pfizer Inc, and UCB., J. Braun Grant/research support from: received honoraria for talks, advisory boards, paid consultancies, and grants for studies from AbbVie (Abbott), Amgen, Biogen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Hospira, Janssen, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer Inc (Wyeth), Roche, Sanofi-Aventis, and UCB, Consultant for: received honoraria for talks, advisory boards, paid consultancies, and grants for studies from AbbVie (Abbott), Amgen, Biogen, BMS, Boehringer, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Hospira, Janssen, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer Inc (Wyeth), Roche, Sanofi-Aventis, and UCB